Climatic Classification and Climatic Change - Gregory, Stanley (ERDKUNDE, 1954)
The aim of this paper is, on the one hand, to show the shift of a number of climatic boundaries over the greater part of Europe during the seventy years from 1871-1940, and, on the other hand, to work out their deviations from the standard period of 1901-1930 usually taken as a basis. Köppen's classification was taken as a basis and the records of the weather stations mentioned in Fig. 1 were used. Since the present improvement of the climate in the temperate latitudes is mainly noticeable in the form of more frequent warm periods and less in a general warming, it was considered more advantageous to use the concept of' climatic years according to Rüssel for the solution of this problem instead of the arithmetic mean values which are generally more usual. Admittedly, the classification of climatic states on an annual, rather than a mean, basis leads to some difficulties - especially with respect to the seasonal distribution of precipitation - so that finally a modification of Köppen's (Table I) criteria had to be carried out. For the standard period 1901 -1930 the climatic regions were mapped on the one hand on the basis of the mean values (Fig. 2) and on the other hand on the basis of an analysis of the climatic years and their main differences were discussed, in particular the distinction between core areas and transition belts made in Fig. 3. The actual width of these boundary belts is given more detailed consideration in Figs. 4 to 6, which were prepared on the basis of a mapping of the climatic boundaries for each of the thirty years. All of these maps clearly reflect the important role, of the larger mountain ranges in stabilizing the boundaries and limiting the width of the transition belts. The changes in the location of the boundaries during the period 1871-1940 have been further elucidated both by comparing the condition of 1901-1930 with that of 1871-1900 (figs. 7 and 8), and by studying the location of the boundaries of five overlapping thirty-year periods (fig. 9). The most prominent of these changes is the advance of the C/D boundary along the Norwegian coast nearly 800 km farther north and across Germany about 500 km to the east.